Why are daylight-linked controls (DLCs) not so spread? A literature review. (September 2016) - Bellia, Laura; Fragliasso, Francesca; Stefanizzi, Emanuela
Abstract: Daylight-linked controls (DLCs) allow to reduce energy costs and to maximize users' comfort. Despite benefits it would provide, DLCs use is rather limited because of different factors: difficulties in design, installation and calibration, problems connected to the evaluation of achievable energy savings, users' reluctance in accepting them. The paper describes each phase of DLCs design process, from early daylight availability evaluations to system installation and calibration, and highlights reasons that limit their spread. Highlights: Each phase of design process affects daylight-linked controls functioning. Control strategy and hardware features influence daylight-linked controls performance. Knowledge about daylight-linked controls is not adequate to guarantee their spread. Software limits affect prediction of energy saving due to daylight-linked controls. Actual performance of daylight-linked systems depends on users' acceptance.